The Correlation of Coping Strategies, Perceived Social Support, and Self-Reported Anxiety among Nursing Students during the COVID-19 Outbreak - Lainsamputty, Ferdy; Gerungan, Nova (STIKep PPNI Jawa Barat, 2024)
Aims: This study aims to investigate the correlation between coping strategies, perceived social support, and anxiety among nursing students during the COVID-19 pandemic. Methods: A descriptive, correlational, cross-sectional study. Total sampling technique was used to recruit 106 nursing students. Data were collected using the Coping Strategies Inventory Short-Form (CSI-SF), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Generalized Anxiety Disorder-7 (GAD-7). Pearson correlation was employed to examine the relationships between key variables. Results: Anxiety was significantly correlated with engagement (r = 0.192, p = 0.049), disengagement (r = 0.264, p = 0.006), emotion-focused engagement (r = 0.222, p = 0.022), and emotion-focused disengagement (r = 0.325, p = 0.001). However, social support and its subscales were not significantly correlated with anxiety (r = -0.007 to 0.147, p > 0.05). Conclusions: The study suggests that students with higher anxiety tend to adopt more coping strategies, suggesting that targeted training, social support networks, and personalized interventions can improve their mental health.